Fe2O3 Nanoparticles Modified 2D N‐Doped Porous Graphene‐like Carbon as an Efficient and Robust Electrocatalyst for Oxygen Reduction Reaction. Issue 14 (11th April 2019) - Ye, Yuzhen; Wang, Bin; Liu, Gaopeng; Xu, Li; Xia, Jiexiang; Li, Huaming
Abstract: As the high expense and poor stability of Pt‐based catalysts have severely limited the commercial applications of cathodic catalysts in fuel cells, the steps towards developing low‐cost and stable catalysts for oxygen reduction reaction (ORR) have never stopped. In this work, we designed a Fe2 O3 nanoparticles decorated 2D N‐doped porous graphene‐like carbon material (Fe(1.0)–N/C‐800) from the one‐step pyrolysis of low‐cost and abundant substrates (β‐cyclodextrin, urea and FeCl3 ) under N2 atmosphere. The doped N can change the charge distribution of C atoms around N atoms and offer active N species such as pyridinic‐N and graphitic‐N to provide more ORR active sites. The appropriate Fe2 O3 nanoparticles encapsulated in the graphene‐like carbon layer can enhance the electron and O2 transfer and boost the ORR process. Therefore, the synergetic effect of Fe2 O3 nanoparticles modifying and N doping can greatly promote the ORR process. The study on the poisoning of Fe 3+ by SCN – further reveals that the Fe2 O3 nanoparticles wrapped in the carbon layer will coordinate with N to form Fe–Nx active sites, which can further enhance ORR activity. Thus, the obtained Fe(1.0)–N/C‐800 electrocatalyst possesses excellent ORR catalytic performance in alkaline media (Eonset =0.937 V, E1/2 =0.832 V) as well as a superior methanol tolerance and long‐term test stability both in alkaline and acidic media. This work leads a simple and cost‐efficient way to fabricate high‐performance ORR catalysts. Abstract : The Fe2 O3 nanoparticles modified 2D N‐doped porous graphene‐like carbon material (Fe(1.0)–N/C‐800) was fabricated from the one‐step pyrolysis of low‐cost and abundant substrates (β‐cyclodextrin, urea and iron trichloride hexahydrate) for the oxygen reduction reaction. Both Fe2 O3 nanoparticles modification and N doping can provide more ORR active sites for the carbon material. Thus, the obtained Fe(1.0)–N/C‐800 electrocatalyst possesses excellent ORR catalytic performance and superior methanol tolerance and long‐term test stability.